2018
DOI: 10.1016/j.gaitpost.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Do spatiotemporal parameters and gait variability differ across the lifespan of healthy adults? A systematic review

Abstract: The findings of this review suggest that most spatiotemporal parameters significantly differ across different age groups. Elderly populations show a reduction of preferred walking speed, cadence, step and stride length, all related to a more cautious gait, while gait variability measures remain stable over time. A preliminary framework of normative reference data is provided, enabling insights into the influence of aging on spatiotemporal parameters, however spatiotemporal parameters of middle-aged adults shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
154
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(179 citation statements)
references
References 57 publications
15
154
3
7
Order By: Relevance
“…The differences in these values are likely explained by differences in stride and height since the average step length in the present study was 0.58±0.05m, compared to 0.66m and 0.61m for Swedish men and 0.59m for Swedish women as reported by Al-Obaidi et al 5 Speed has been associated with variables such as step length, limbs length, height and cadence. 3 In this study, the step length was 0.58m and the average height was 166 cm, which are similar to those reported in studies conducted in similar age groups, with step lengths between 0.59m and 0.70m and heights that oscillate between 164cm and 180cm. 5,17,22 To make the data comparable between populations of different heights, several standardizations that include height, step length or limb length are frequently used.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The differences in these values are likely explained by differences in stride and height since the average step length in the present study was 0.58±0.05m, compared to 0.66m and 0.61m for Swedish men and 0.59m for Swedish women as reported by Al-Obaidi et al 5 Speed has been associated with variables such as step length, limbs length, height and cadence. 3 In this study, the step length was 0.58m and the average height was 166 cm, which are similar to those reported in studies conducted in similar age groups, with step lengths between 0.59m and 0.70m and heights that oscillate between 164cm and 180cm. 5,17,22 To make the data comparable between populations of different heights, several standardizations that include height, step length or limb length are frequently used.…”
Section: Discussionsupporting
confidence: 89%
“…All these aspects allow accurately interpreting the outcomes. [3][4][5] To provide a solution for the measurement issues mentioned above and to perform a more objective evaluation, high-quality systems such as gait analysis laboratories have been designed. These laboratories are considered as one of the most comprehensive and sophisticated evaluation methods since they provide an objective and quantitative assessment of the different parameters of human gait, 2 which are essential and necessary for the proper evaluation and diagnosis of gait alterations, and, also, for therapeutic follow-up and making clinical decisions (surgeries, orthoses, prosthesis).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, if we had collected data on the same subject during walking, the use of different foot markers to calculate step width would have resulted in different coefficient of variations, while the standard deviations of the step width would have been the same (assuming that the foot is a rigid segment and there is no rotation). This is supported by a recent literature review that showed that the coefficient of variation of step width exhibited large differences between studies [69]. Finally, the coefficient of variation is applicable only to ratio data, and the step width is considered interval data as it is not bounded by a meaningful zero point [46,70].…”
Section: Computation Of Step Width Variabilitymentioning
confidence: 80%
“…The healthy control group in this study was not age matched with the BVP group and there were nonsignificant age differences between the three BVP groups. However, we do not think that this would influence our findings as a number of studies have shown that gait variability (the focus of the current study) in healthy young and older adults is not significantly affected by (healthy) ageing (Herssens et al 2018;Hollman et al 2011).…”
Section: Discussionmentioning
confidence: 76%